Association of thyroid dysfunction and hyperprolactinemia with subfertility in women at a tertiary care hospital - Chowdhury, Jannatul Ferdous; Aziz, Effat; Haque, M. Mahbobul; Sarmin, Rubab; Tasnim, Maliha; Husain, Mahzabin; Sultana, Tasnia; Akter, Salma (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2025)
Background: Endocrine abnormalities, particularly thyroid dysfunction and hyperprolactinemia, are recognized contributors to female subfertility. Both disorders are potentially correctable causes of impaired reproductive function through their effects on the hypothalamic-pituitary-ovarian axis. This study aimed to investigate the association between thyroid dysfunction and hyperprolactinemia with subfertility in women attending a tertiary care hospital in Bangladesh. Methods: This case-control study was conducted at the department of obstetrics and gynecology, BIRDEM General Hospital, from January 2022 to March 2024. A total of 100 women were enrolled in the study: 50 subfertile (cases) and 50 fertile (controls). The demographic and clinical characteristics were recorded. Serum TSH, FT3, FT4, and prolactin levels were measured using chemiluminescent magnetic microparticle assays. Thyroid status and prolactin levels were compared. The correlation between TSH and prolactin levels was assessed using Pearson’s test. Results: Thyroid dysfunction was observed in 16% of subfertile women compared to 6% of controls. Hyperprolactinemia was significantly more frequent among cases (32% versus 10%, p=0.007). A moderate positive correlation was found between TSH and prolactin in the case group (r=+0.537, p<0.001) and a weak positive correlation in the control group (r=+0.263, p=0.065). Conclusions: Thyroid dysfunction and hyperprolactinemia were more prevalent among subfertile women and were strongly associated. Routine screening for thyroid and prolactin abnormalities should be incorporated into infertility evaluations, as correction of these disorders may restore fertility.